Methane production characteristics and microbial community dynamics of mono-digestion and co-digestion using corn stalk and pig manure. (23rd February 2017) - Wang, Min; Zhou, Jun; Yuan, Yue-Xiang; Dai, Yu-Mei; Li, Dong; Li, Zhi-Dong; Liu, Xiao-Feng; Zhang, Xue-Ying; Yan, Zhi-Ying
Abstract: This study investigated methane productions and the microbial communities in the batch anaerobic digestion process with the mono-digestion of corn stalk (CS) and pig manure (PM), and the co-digestion of them. Co-digestion showed the best methane performance, the cumulative methane yield, 256.57 mL·gVS −1 ; methane production potential, 281.55 mL·gVS −1 ; maximum methane production rate, 10.17 mL·d −1 ·gVS −1 ; and lag phase, 4.24 d. Moreover, co-digestion achieved a more suitable microenvironment including pH, FA and FVFA compared to mono-digestions. Results of high-throughput sequencing indicated that in co-digestion the dynamic changes of relative abundances of phyla and predominant genera were very small and community structure presented a stable status. Acetoclastic pathway was the main biochemical pathway of methanogenesis in co-digestion and mono-digestion of PM, and the growth rate of Methanosaeta in co-digestion was higher. So suitable microenvironment in co-digestion resulted in high growth rate of methanogens and stable microbial community, and leaded to the high methane production. Highlights: Co-digestion and mono-digestion with corn stalk and pig manure. Kinetic analysis by Gompertz equation was used to prove that co-digestion had higher efficiency than mono-digestion. Co-digestion contributed to achieving a suitable microenvironment including pH, FA and FVFA compared to mono-digestions. The microbial community structure in co-digestion presented more stable status by high-throughput sequencing analysis.